Insight or ignorance: How collaborative history in a workgroup fits with project type to shape performance - Parker, Owen N.; Mui, Rachel; Bhawe, Nachiket; Semadeni, Matthew (Journal of business research, 2022)
•Workgroup members’ prior collaborations shape current project outcomes.•Psychological safety from collaboration can promote “shared misunderstanding”•Firms must match the type of workgroup collaborative history to the project’s focus.•Internal (within-firm) collaborative history works better with exploitative projects.•External (outside-firm) collaborative history works better with imitative projects. According to the knowledge transfer literature, members of a project workgroup who share collaborative history possess a “shared understanding” thought to increase psychological safety and efficiency, thereby improving current project performance. But knowledge misfit can occur depending on where they have previously collaborated (internal or external to the focal firm) and the type of project currently pursued. We contend that misfit engenders “shared misunderstanding” where prior collaborators impose irrelevant knowledge onto a project, undermining performance. We extend research on knowledge transfer and human capital mobility by predicting that internal collaborative history helps exploitative.